Efektivitas Program Kaliber (Kawal Pemilu Bersih) Fakultas Hukum Muhammadiyah Sumatera Barat dalam Penyelenggaran Pemilu di Kecamatan Mandiangin Koto Selayan Kota Bukittinggi - Fahmi, Muhammad Zaky; Leonardo, Ari; Saputra, Feri Andri; Kurniawan, Ahmad; 'Ibad, Reza Irsyadul; Arman, Zuhdi (Gorontalo Law Review, 2024)
The purpose of this research is to determine the effectiveness of the Clean Election Monitoring activity and to understand the community's understanding of money politics during the election period in Mandiangin Koto Selayan District. This research utilizes a qualitative research method with both normative juridical and empirical juridical types to observe legal realities within society. The study is conducted in Mandiangin Koto Selayan District, Bukittinggi City, West Sumatra. Data is collected through observation, interviews, and documentation. Data analysis techniques used include data collection, data reduction, data presentation, and drawing conclusions, following the Miles and Huberman (1992) methodology. The findings of this research explain that the Clean Election Monitoring activity has not been effective due to the limited socialization efforts targeting specific groups, resulting in incomplete information acceptance by the community, lack of public awareness in rejecting money politics, insufficiently trained personnel, and inadequate facilities.